Self-assessment of Internal Quality Assurance Mechanisms: An Empirical Investigation - Kaggwa, Fred; Nabachwa, Sarah; Kyoshaba, Martha; Kalungi, Dickson; Ambros, Atuheire Izaara; Nakakeet, Robinah F.; Agum, Solomon (The Arab Journal For Quality Assurance in Higher Education, 2023)
This study examines the internal quality assurance mechanisms (IQAMs) at Mbarara University of Science and Technology (MUST) in Uganda through a self-assessment. A descriptive design and quantitative method are employed to investigate various quality aspects from all faculties and all units of MUST. The units of inquiry were (i) the internal stakeholders of MUST i.e. current staff and students, and (ii) the MUST Alumni. Participants were sampled using stratified simple random sampling where faculties and specific programs formed the various strata. The student samples were drawn from the admission lists while the alumni email contacts were drawn from the archived information in the Academic registrar’s office. Staff lists were drawn from the Human Resources office. The study utilized a structured questionnaire based on the Inter-University Council of East Africa (IUCEA) model. Based on the target population and samples, 384, 76, and 371 responses were received from students, staff and alumni respectively. The study revealed that IQAMs were implemented in various areas including teaching and learning, research and innovations, and community outreach, but gaps existed in policies for skills development and community engagement. While the university had established quality assurance policies, there were concerns regarding their awareness and implementation. Diverse opinions among students and staff emphasized the importance of considering multiple perspectives. Alumni feedback highlighted positive outcomes in employability and program satisfaction, but suggested improvements in integrating practical components and enhancing university-industry collaborations. Based on the findings, recommendations were made to MUST, including the development of specific policies, strengthening implementation strategies, enhancing student engagement, addressing staff viewpoints, fostering alumni involvement, and strengthening university-industry connections. These recommendations aim to enhance internal quality assurance mechanisms and overall education quality. The study provides valuable insights into quality assurance practices at MUST and emphasizes the need for continuous monitoring and improvement to sustain educational quality. Future work should conduct a qualitative study to gain a deeper understanding of the self-assessment study and also the underlying reasons, motivations, and experiences that could have influenced the aforementioned quantitative findings.
Keywords: Internal Quality Assurance Mechanisms; Self-assesment; Continuous quality improvement; Stakeholder perspectives; Policy implementation strategies